Improving Family Stability and Substance Use Recovery for Families in the Child Welfare System: Impact of Ohio's Statewide System Improvement Program. (20th August 2020) - Crane, D.; Bailey, E.; Adjei‐Tabi, L.; Farrington, B.; Monroe, K.; Watson, J.; Applegate, M.; Doogan, N.; Eisner, C.
Abstract : Research Objective: Family drug courts (FDCs) and other multi‐system strategies are increasingly used to address the needs of families involved in the child welfare system who are affected by substance use disorders. Ohio's Statewide System Improvement Program (SSIP) was established to expand the scale and service scope of existing FDCs and coordinating care across court, child welfare, and behavioral health systems. This study was conducted to evaluate the impact of SSIP on family stability and recover outcomes over time. Study Design: Propensity Score Matching was applied to compare outcomes for eligible families with and without exposure to SSIP and identify characteristics of families most likely to enroll in FDC. Logistic and linear regression analyses were conducted to identify differences in temporal trends among the SSIP intervention and matched comparison groups. Population Studied: Administrative data from state agencies and local FDCs were linked using a deterministic linkage process. Statewide Automated Child Welfare Information System (SACWIS) data were gathered to identify cases of child maltreatment[i] where substance use was a contributing factor[ii] and to assess family stability (eg, out‐of‐home placement, subsequent maltreatment, and reunification). Medicaid administrative data provided information about clinical diagnoses and treatment. Behavioral health treatment episode data provided information related to social determinants of health (eg, employment). Principal Findings: The SSIP FDC participants demonstrated significant improvement (reduction) over time in out‐of‐home placement (2015‐2017), while there was no improvement over time in the comparison group (OR = 1.70, P < .05). Counties that implemented SSIP demonstrated improvement over time (2014‐2017) relative to the comparison group in the following areas: behavioral health treatment retention (β = 0.26, P < .01); medication‐assisted treatment retention (β = 0.45, P < .05); length‐of‐stay in out‐of‐home placement (OR = 1.15, P < .05); and placement with kin (OR = 1.22, P < .01). Among 1, 695 family case episodes eligible for FDC, only 15.6% were enrolled in a FDC. Standardized differences scores revealed family characteristics associated with FDC enrollment including: white race ( P < .001), history of child maltreatment ( P < .001), and parent with mental illness ( P < .001). Conclusions: This finding suggests that SSIP program elements that focus on coordination of behavioral health services and judicial involvement to monitor participation may have had a significant positive impact over time, as the key elements of the model were put into practice. Implications for Policy or Practice: While FDCs are showing promising results in the counties where the programs are in place, more work is needed to ensure equal access to FDCs and identify effective practices to be spread. Linked administrative datasets can be used to measure the impact of child welfare interventions on individual‐ and family‐level outcomes across systems of care with minimal data collection burden. Future work could include a cost‐benefit analysis as costs were not the primary endpoints in this analysis. Child maltreatment defined by child abuse or neglect based on Ohio's Comprehensive Assessment Planning Model‐Interim Solution Policy Manual and includes admission of by the person(s) responsible; adjudication; other forms of confirmation; circumstantial or isolated indicators; or a determination by a caseworker based upon assessment/investigation. Substance use involvement identified by report of substance use on the intake record, family assessment, or placement file. Primary Funding Source: United States Department of Justice Office of Juvenile Justice and Delinquency Prevention and the Ohio Supreme Court.